Baseline study on the enforcement of Syariah maintenance court order in Selangor - Mohd Zin, Najibah; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Ibrahim, Kamilia; Md Said, Helmi (2015)
This study examines problems on the enforcement of maintenance orders of the Syariah Courts. Despite the fact that Syariah courts are guided by comprehensive statutory laws, however, complaints on matters related with maintenance orders are still unresolved. Therefore this study is undertaken to examine and identify problems that have caused the failure to enforce maintenance orders. Studies conducted show that women and children are the most affected group due to the weak enforcement of the Syariah maintenance court orders. This research uses qualitative approach based on legal doctrine and data. Data are obtained through scrutiny of the files from the court and informants consisting of officers from the Syariah court as well as clients of the court. The study discloses an obvious co-relation between complex and lengthy processes, unnecessary time consuming and costs inefficiency with the enforcement order of maintenance. This article is preamble to a an envisaged study on the enforcement of maintenance order in the Syariah Court of which the result will be useful for further improvement of the existing legal provisions in Malaysia.